(untitled) (Direito e Humanidades, 2025)
This article analyzes the impact of the Supreme Federal Court’s decision in the case of the Fundamental Precept Violation Claim 188, which altered the methodology for distributing resources from the Salário-Educação, one of the main mechanisms for funding basic education in Brazil. Through a legal analysis and projected data for 2024, the article investigates how the change in the distribution criterion, which now considers exclusively the number of enrollments in primary education, supports the Union’s redistributive function, fostering greater equity among the states. The conclusion suggests that states in the North and Northeast will significantly benefit from the Supreme Court’s decision, while states with higher tax collection capacity will face challenges in readjusting their budgets within the new distribution framework.